A Study of various reforms during Tughlaq period - Harshit; Kumar, Naveen (Innovative Research Thoughts, 2017)
There have been five dynasties during the sultanate period. Tughlaq dynasty comes in the middle and late dynasties. Ghiyasuddin Tughlaq was the father of the Tughlaq Dynasty. Alauddin Khilji (1301-1316) appointed Ghiyasuddin Tughlaq as the Subedar and Border Guard of Dipalpur in 1305 AD. He had earlier distinguished himself by acts of gallantry in Multan and Dipalpur, where he had also served in the Mongol-backed Rajput wars. Alauddin used him as one of the "distinguished Amirs." On the evening of 8 September 1320, he was crowned sultan. This is represented from the sources: When He sat on a throne, He had to contend with various challenges, including the complete dissolution of the Alauddin regime, which had lasted for almost two decades. Minister of finance Mubarakshah and Governor of Khuzestan Khusroshah drained the government treasury. “Amirs” ought to become self-sufficient. Fakhruddin Muhammad Jauna Khan, who was also granted the title of ulugh khan, became the new Delhi Sultan following the tragic death of his father, Ghiyasuddin Tughlaq, in 1325. During his rule, the sultanate achieved a remarkable historical milestone. During his rule, the Delhi Sultanate gained influence over a large portion of the Deccan and South India. This marked the zenith of the Delhi Sultanate's territorial expansion. Contrary to what is popularly accepted, the fall of the sultanate also started at this period.